2019
DOI: 10.1016/j.trsl.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular discoveries and treatment strategies by direct reprogramming in cardiac regeneration

Abstract: Cardiac tissue has minimal endogenous regenerative capacity in response to injury. Treatment options are limited following tissue damage after events such as myocardial infarction. Current strategies are aimed primarily at injury prevention, but attention has been increasingly targeted toward the development of regenerative therapies. This review focuses on recent developments in the field of cardiac fibroblast reprogramming into induced cardiomyocytes. Early efforts to produce cardiac regeneration centered ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 97 publications
(159 reference statements)
0
7
0
1
Order By: Relevance
“…More information on the currently available protocols to generate PSC-derived CMs and criteria to distinguish the different subtypes of PSC-derived CMs can be found in some recent reviews (116,127,(132)(133)(134). An alternative strategy to generate CMs from non-CMs is through the direct cardiomyogenic reprogramming of fibroblasts by (cardiomyogenic) transcription factors, miRNAs or small molecules (135,136). However, thus far, the reprogramming efficiencies are low and the resulting so-called induced CM-like cells (iCMs) are rather immature and comprise a mixture of different CM subtypes, limiting their suitability for cardiac disease modeling.…”
Section: (Human) Psc-derived Atrial(-like) Cmsmentioning
confidence: 99%
“…More information on the currently available protocols to generate PSC-derived CMs and criteria to distinguish the different subtypes of PSC-derived CMs can be found in some recent reviews (116,127,(132)(133)(134). An alternative strategy to generate CMs from non-CMs is through the direct cardiomyogenic reprogramming of fibroblasts by (cardiomyogenic) transcription factors, miRNAs or small molecules (135,136). However, thus far, the reprogramming efficiencies are low and the resulting so-called induced CM-like cells (iCMs) are rather immature and comprise a mixture of different CM subtypes, limiting their suitability for cardiac disease modeling.…”
Section: (Human) Psc-derived Atrial(-like) Cmsmentioning
confidence: 99%
“…GATA4 is currently the most studied cardiac transcription factor (Rasekhi et al, 2017). Like miR-133, GATA4 also inhibits the Snai1 pathway (Werner et al, 2019), therefore, it is speculated that miR-133 and GATA4 play a synergistic role in cardiac reprogramming. It has been shown that combined injection of miR-133, miR-1, miR-499, and miR-208 into ischemic myocardial tissue induces fibroblasts to reprogram and transform into cardiomyocyte-like cells that then improve cardiac function (Cheng et al, 2019).…”
Section: Reprogrammingmentioning
confidence: 99%
“…The combination of miR-1and miR-133 with GMTH cocktail generated significantly more matured iCMs [ 93 , 100 ]. Supplementing the viral GMT, GMTH, or GMTHMyMe cocktail with a TGF-β inhibitor or synthetic mimics of miR-1, miR-133, or miR-590 increased the CM reprogramming efficiency and speed of mouse, pig, or human cells, which provided new insight into the molecular mechanism of cardiac reprogramming [ 80 , 101 , 102 ].…”
Section: Direct Cardiac Reprogramming For Heart Regenerationmentioning
confidence: 99%